Cadmium determination in Chilean blue mussels Mytilus chilensis: Implications for environmental and agronomic interest. Issue 2 (April 2018) - Blanc, J. Max; Molinet, Carlos; Subiabre, Ricardo; Díaz, Patricio A.
Abstract: Cadmium is present in agricultural soil composition and is assimilated by plants. The mussel industry generates large volumes of calcareous valves as a byproduct of processing in factories. This solid waste is ground, stored and disposed of in the form of agricultural supplies near production areas in almost all regions of the world. Cd content was recorded in these calcareous substrate by-products of industrial processes. In this study, mussel shells were investigated in three areas in the sea of Chile; two areas with high aquaculture activity and one in a non-production area. Mass Spectrometry was used for [Cd] readings. There are no significant differences (p = 0.92) in [Cd] between the studied areas. Additionally, the [Cd] observed in valves was also similar relative to different depths. The low [Cd] observed in valves (~ 0.014 ± 0.0049 mg Cd kg − 1 dry) suggests the potential use of this industrial byproduct in agricultural applications. Highlights: Significant difference in [Cd] between zones and sampling depths were not observed. The [Cd] in valves shows an identical seasonal pattern between growing areas and natural banks. The [Cd] in valves, soft tissues and hepatopancreas do not present a significant correlation. The [Cd] in valves are independent of that recorded in soft tissues. The low [Cd] observed in mussels' shells of southern Chile allows their use as a corrector of acidity in soils.